2018
DOI: 10.1002/chem.201801169
|View full text |Cite
|
Sign up to set email alerts
|

La5Ti2Cu0.9Ag0.1S5O7 Modified with a Molecular Ni Catalyst for Photoelectrochemical H2 Generation

Abstract: The stable and efficient integration of molecular catalysts into p-type semiconductor materials is a contemporary challenge in photoelectrochemical fuel synthesis. Here, we report the combination of a phosphonated molecular Ni catalyst with a TiO -coated La Ti Cu Ag S O photocathode for visible light driven H production. This hybrid assembly provides a positive onset potential, large photocurrents, and high Faradaic yield for more than three hours. A decisive feature of the hybrid electrode is the TiO interlay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Very recently, Domen and co‐workers constructed a Ni catalyst ( 8, Figure 2) on the surface of TiO 2 ‐coated La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 . When the nickel catalyst was anchored on a La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 /TiO 2 electrode, an onset potential of +0.65 V versus RHE was obtained with a photocurrent of 0.6 mA cm −2 at 0 V versus RHE 52…”
Section: Benchmarks Of Hybrid System Assemblies For Photoelectrochemimentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently, Domen and co‐workers constructed a Ni catalyst ( 8, Figure 2) on the surface of TiO 2 ‐coated La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 . When the nickel catalyst was anchored on a La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 /TiO 2 electrode, an onset potential of +0.65 V versus RHE was obtained with a photocurrent of 0.6 mA cm −2 at 0 V versus RHE 52…”
Section: Benchmarks Of Hybrid System Assemblies For Photoelectrochemimentioning
confidence: 99%
“…In addition, the semiconductor electrode should possess long‐term stability under light irradiation conditions for water splitting reactions. To date, numerous semiconductor photoelectrodes have been developed for PEC water splitting, including p‐Si,25–35 p‐GaP,36–40 InP,41,42 Cu 2 O,43,44 CdSe quantum dots (QDs),45–49 CdS QDs50, p‐GaInP51, and La 5 Ti 2 Cu 0.9 Ag 0.1 S 5 O 7 52 for water reduction and α‐Fe 2 O 3 ,53–66 WO 3 ,67–75 BiVO 4 75–84 and n‐Si85 for water oxidation. For more information about the properties of the semiconductors, including the conduction (CB) and valence band (VB), stabilities as a function of pH values, the light absorption behavior, and advanced preparation methods for different morphologies, readers are invited to refer to related review papers 86–89…”
Section: Fundamentals Of Hybrid Systems For Photoelectrochemical Watementioning
confidence: 99%
“…This groundbreaking design offered the possibilities of varying the semiconductor electrodes, the photosensitizers, and the co‐catalysts used. This report has been followed by a number of recent variations where molecular co‐catalysts for H 2 evolution and CO 2 reduction were attached on the photocathodes instead of the photoanodes.…”
Section: Pecs For Water Splittingmentioning
confidence: 99%
“…22 Full details of the synthetic procedures, the device characterisation and SEM images are provided in the supporting information, Figs S2.1-3. The molecular catalyst was first immobilized overnight onto the sputtered TiO 2 (without the TiO 2 -meso) by soaking the photoelectrode in dry methanolic solution (0.5 mM NiP), 19,23,24 and from now on labelled as Sb 2 Se 3 /CdS/TiO 2 /NiP. It was removed from the soaking solution, thoroughly washed in methanol to remove the non-chemisorbed catalyst and dried under vacuum.…”
mentioning
confidence: 99%
“…All the photoelectrochemical tests were done under 100 mW cm 2 illumination (unless otherwise stated) and with  > 340 nm in 0.1 M Na 2 SO 4 at pH 3. pH 3 was chosen due to past studies that showed NiP was most active at this pH. 23,25 Figure 2 shows a photocurrent of only 16 A cm 2 at 0 V vs RHE, which exceeds only slightly the current in the absence of any catalyst (3 A cm 2 for Sb 2 Se 3 /CdS/TiO 2 , Fig S2 .4). The spikes in the light chopped Linear Sweep Voltammetry (LSV) of Sb 2 Se 3 /CdS/TiO 2 /NiP demonstrated that the photoelectrons are not being utilised at a fast-enough rate by the catalyst, instead recombination is dominating.…”
mentioning
confidence: 99%